2019
DOI: 10.4025/actascianimsci.v41i1.43871
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of consumer willingness to buy cattle meat: An analysis of survey data from three Brazilian cities

Abstract: Brazil is currently undergoing a process to establish new patterns of consumption habits and the implementation of a new concepts of meat quality. The process emphasizes the quality of information delivered to consumers, which is part of the new approach to meat quality and food safety. The objective of this article is to investigate the attributes considered important when buying beef, knowledge about the production process, labelling, cuts and characteristics of the animals. The study included 276 consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…Os quatro bairros que mais consomem são: Santa Luzia com 19,5% de consumidores, Ramalho Júnior com 14,4% dos consumidores, Mário Negreiros da Fonseca com 11,9% dos consumidores e Maresia com 11% dos consumidores. Esse resultado possui grande importância, pois pode apontar para o varejo em quais regiões, o seu produto será mais procurado (Monteschio et al, 2020;Mottin et al, 2019;Passetti et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os quatro bairros que mais consomem são: Santa Luzia com 19,5% de consumidores, Ramalho Júnior com 14,4% dos consumidores, Mário Negreiros da Fonseca com 11,9% dos consumidores e Maresia com 11% dos consumidores. Esse resultado possui grande importância, pois pode apontar para o varejo em quais regiões, o seu produto será mais procurado (Monteschio et al, 2020;Mottin et al, 2019;Passetti et al, 2020).…”
Section: Resultsunclassified
“…O consumo de carne poder ser influenciado por particularidades que envolvem o desenvolvimento regional, aspectos demográficos, socioeconômicos, climáticos, qualidade alimentar e saúde do produto, gostos e hábitos pessoais, bem como a precificação (Kiran et al, 2018;Monteschio et al, 2020;Mottin et al, 2019).…”
Section: Gráfico 3 Renda Mensal Dos Entrevistadosunclassified
“… Mottin et al (2019) in a study on the cattle meat consumption in Brasilia found that the presentation of the product is regarded as the most important attribute at the time of purchase.…”
Section: Demand For Rabbit Productsmentioning
confidence: 99%
“…In this way, the consumer has to observe at the moment of purchase the possible quality indicators to make the judgment and decide for the purchase. However, the consumer's lack of knowledge about the different quality attributes of beef (such as odor, flavor, tenderness, and overall acceptability), and how they vary within the same cuts (Eiras et al, 2017;Guerrero et al, 2018;Mottin et al, 2019;Prado et al, 2015a;Vital et al, 2018) present difficulties at the purchase time.…”
Section: Introductionmentioning
confidence: 99%
“…This is because some indicators cannot be perceived by the consumer at the time of purchase, unless some additional information is provided (Grunert, 1995;Saeed & Grunert, 2014). Thus, for beef, perceived intrinsic quality cues are: color, freshness and visible fat; and the perceived extrinsic quality cues are: price, point of sale, presentation, designation of origin and promotion of the meat (Acebrón & Dopico, 2000;Bredahl, 2004;Mottin et al, 2019;Troy & Kerry, 2010).…”
Section: Introductionmentioning
confidence: 99%